Prophylaxis of allergic rhinitis - Samoliński, Bolesław; Rapiejko, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
The authors discuss the issue of the prophylaxis of allergic rhinitis. The current knowledge on most common aeroallergens is presented. Plant species that are the cause of allergic symptoms in Poland as well as pollen and mould spores monitoring systems are described. The methods of the reduction of aeroallergens exposure are analysed.